(untitled) (The Planet, 2023)
Introduction: Cervical cancer is a significant health issueworldwide. Cervical cancer is a leading cause of cancerdeath among women. Understanding the impact ofdemographic factors on cervical cancer rates is essentialfor developing effective public health policies andprograms in Bangladesh. The aim of the study was todetermine the socio-demographic characteristics amongVIA-positive cervical cancer cases in Bangladesh.Methods and materials: This cross-sectional study wasconducted at the VIA center at the Institute of Child andMother Health in Matuail, Dhaka, from November 2017 toOctober 2018. A total of 95 women who had VIA testspositive at the center during the study period made up thestudy population. Results: Mean age of patients35.89±8.88 years, majority had a family income of 10000-20000 taka, and had watery P/V discharge (31.6%). The most common type of irregular P/Vbleeding was intermenstrual bleeding (40.0%). The majority of patients were married at 18years with a mean age of marriage 16.11±1.84 years and had been married for 10-20 years.The majority of patients had para 2, age of first delivery ≤18 years, and took the pill forcontraception. Histopathological results showed that the majority of patients had chroniccervicitis (33.6%), followed by moderate dysplasia (37.8%), mild dysplasia (16.8%), invasivecarcinoma (7.5%), and chronic cervicitis with sq. metaplasia (4.2%). Conclusion: Increasingaccess to cervical cancer screenings and contraception, as well as educating about delayingmarriage and childbearing, could help reduce cervical cancer risk in lower-income population through targeted interventions.